Creating communities of practice for fostering second language learning in people in crisis - Chrabaszcz , Anna; Anisimova, Vera; Antropova, Julia; Bikina, Daria; Menukhova, Anna; Mirabo, Sandra; Odnoshivkina, Victoria; Shcherbakova, Anna; Tikhomirova, Anna; Zmiievska, Tetiana (East European Journal of Psycholinguistics, 2022)
This paper describes two volunteer-based nonprofit initiatives, COMMON and Speak Up For Peace, which originated as a response to the humanitarian crisis caused by the invasion of the Russian Federation of Ukraine. The initiatives function as communities of practice that provide free online foreign language instruction to people in crisis (predominantly Ukrainian refugees). We conducted an online survey in a subset of language instructors (N = 75) and participating people in crisis (N = 102) with the goals 1) to assess the effectiveness of provided language instruction, 2) to gain a better understanding of the participating learners’ and teachers’ experiences and attitudes towards their learning and teaching, respectively, 3) to identify the main challenges and issues that learners and teachers face while participating in the projects, and 4) to gauge the viability of these and similar volunteer-based language projects for people in crisis and refugees in the future. The survey revealed a significant improvement in proficiency and motivation of participating people in crisis to learn a new language. Additionally, participating in the projects was associated with overall positive emotional and psychological benefits, for both learners and teachers. Among the most common issues related to learning and teaching in the context of the projects were student absenteeism and attrition, work balance, and teacher training. Overall, the study revealed interesting insights about perceived attitudes toward learning and teaching in students and instructors, respectively. It may be of interest to educators, language instructors and policymakers working with refugee groups and people in crisis.Disclosure Statement No potential conflict of interest was reported by the authors.